An Natural Material Collage Develops Fine Motor Skills in Early Childhood: Kolase Bahan Alami Mengembangkan Keterampilan Motorik Halus pada Masa Kanak-kanak Awal - Aflia Irwan; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Fine motor skills constitute a fundamental domain of early childhood development because they underpin writing readiness, hand–eye coordination, and creative expression. Specific Background: Learning activities that engage children in manipulating small objects, particularly art-based tasks such as collage, provide practical opportunities to train finger strength, precision, and visual–motor coordination. Knowledge Gap: However, limited research has examined the implementation of collage activities using locally available natural materials within authentic kindergarten classroom contexts and the factors that support or hinder their use. Aims: This study aimed to analyze the implementation of collage activities using natural materials to develop fine motor skills in children aged 5–6 years at an Islamic kindergarten. Results: Using a qualitative phenomenological approach with data from observations, interviews, and documentation involving teachers and 17 students, the study found that activities employing banana leaves, seeds, and twigs trained children’s abilities to cut, tear, paste, and arrange materials according to patterns while maintaining accuracy and control. Teacher facilitation, material availability, and student engagement supported successful implementation, whereas limited time, insufficient tools, and low parental understanding constrained it. Novelty: The study highlights the educational value of environmentally sourced materials integrated into structured classroom practice as a meaningful, context-based learning medium. Implications: Nature-based collage activities can serve as an accessible, low-cost strategy for stimulating fine motor development while simultaneously fostering creativity, concentration, and environmental awareness in early childhood education. Highlights: Children demonstrated improved precision and coordination through tearing, cutting, and assembling tasks. Active facilitation by teachers and accessible environmental resources supported successful classroom implementation. Time constraints, limited equipment, and insufficient parental awareness emerged as primary barriers. Keywords: Fine Motor Skills; Natural Materials; Collage Activities; Early Childhood Education; Qualitative Study